The Digital Transformation of Da'wah in the Methods of Conveying Islamic Teachings in the Contemporary Era - Bilqis Nidaul Khair Daulay (Penerbit Hellow Pustaka, 2026)
The advancement of digital technology has significantly altered patterns of religious communication, particularly regarding the practice of Islamic dakwah (preaching). Dakwah previously conducted through conventional means such as mosque pulpits and religious study circles has now transformed into the digital realm via social media platforms like YouTube, Instagram, TikTok, and podcasts. This article aims to analyze the transformation of digital dakwah and the methods of conveying Islamic teachings in the contemporary era. The study employs a library research method with a descriptive-qualitative approach. The findings indicate that digital dakwah is faster, interactive, and capable of reaching a global audience; however, it also presents challenges such as disinformation, the fragmentation of meaning, and a shift in religious authority from traditional scholars (ulama) to content creators. Consequently, there is a need for dakwah strategies grounded in digital literacy, Islamic communication ethics, and the reinforcement of credible scholarly authority.